Costa Rica : Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper presents key findings of the Financial System Stability Assessment for Costa Rica. The Costa Rican financial system exhibits some immediate strengths deriving from an environment with limited historic volatility and a predominant state participation in financial intermediation. Nonetheless, important underlying macroeconomic and structural tensions could undermine the stability of the system in the event of a major shock, or compromise its medium-term sustainability should tensions continue to accumulate. Main sources of tension on the macroeconomic front are a large fiscal deficit and a high public debt as well as a high and rising dollarization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet